Improving Student’s Vocabulary Mastery Through Crossword Games - Yuliyanah Sain; Eka Setyowati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to improve English learning outcomes through the application of the Crossword puzzle strategy. Type of classroom action research (CAR). The sequence of research activities includes: (1) planning, (2) Implementation, (3) observation, (4) documentation. This classroom action research was conducted at SMP N 5 KENDARI. of class VIII, which consisted of 35 students, they were 16 male and 19 female students. And in collecting data, the researcher used observation technique, tests measuring learning outcomes. The result showed that the use of the crossword puzzle strategy in English learning can improve student learning outcomes starting to 44% in cycle 1, then the learning outcomes increased in cycle II by 96%.